Extended electrocardiographic monitoring in patients on chronic haemodialysis and after renal transplantation - Lee-Jones, Scott (Department of Medicine, 2023)
Background Chronic Kidney Disease (CKD) and chronic haemodialysis are associated with cardiovascular disease. Despite the increased risk of sudden cardiac death, few studies to date have described the burden of arrhythmias in this population. The aim of this study was to determine the prevalence, type and timing of arrhythmias by means of implantable loop recorder (ILR) monitoring in patients with CKD on chronic haemodialysis. Methods In this prospective cohort study, ILR's were implanted in twenty patients with CKD on the Renal Replacement Programme at Groote Schuur Hospital in Cape Town. Clinical, electrocardiographic and echocardiographic parameters were collected. We reviewed ILR recordings obtained between August 2015 and July 2018 and analysed arrhythmic events in relation to clinical parameters and temporal relation to dialysis sessions. Results In this cohort of 17/20 patients (1 died prior to ILR download and 2 lost to follow-up), the median age was 38 years (IQR 27.5 – 45) and left ventricular ejection fraction (LVEF) 62% (48 – 73). Clinically significant arrhythmias included atrioventricular (AV) block (n=24), atrial fibrillation (n=12) and non-sustained ventricular tachycardia (n=2). Most (57.4%) arrhythmic events occurred in the long interdialytic period between dialysis sessions. One patient with high degree AV block detected by ILR received a permanent pacemaker. Arrhythmic events were less prevalent after renal transplantation (6/17 during study period). Conclusion We have demonstrated that there is potential clinical utility of ILR monitoring in this population, which have a high risk of largely asymptomatic, clinically significant arrythmias. Larger studies are required to validate our findings.